Evaluation of hepatic injury in acute carbon monoxide-poisoned patients in emergency department. (July 2020) - Kim, SJ; Oh, HS; Cha, YS; Kim, MY; Kim, H
Introduction: The affinity of hemoglobin for carbon monoxide (CO) is 250 times higher than that for oxygen. Therefore, exposure to CO leads to a reduction in oxygen delivery to tissues, resulting in cellular hypoxia and affects whole body. Hepatic dysfunction in critically ill patients is related to poor outcome, but few studies have been conducted on this subject that occurs after CO poisoning. This study aims to conduct a study of hepatic injury in CO-poisoned patients in emergency department (ED). Methods: This retrospective observational study collected data from patients who were diagnosed with acute CO poisoning at the ED between June 2011 and May 2018 in local tertiary-care hospital (Wonju, Republic of Korea). The primary end point of this study was to describe the prevalence of hepatic injury in acute CO-poisoned patients. The secondary goals were to investigate the recovery trends of hepatic injury caused by acute CO poisoning and the relation to neurologic outcome and mortality. Results: Eight hundred ninety-four patients were enrolled in the final analysis, 128 cases (14.3%) had subclinical hepatic injury and 15 (1.6%) cases had hepatic injury. The relationship with mortality was not statistically significant. However, the hepatic injury group was higher incidence of intensive care unit admission and other complications. Patients in the hepatic injury group recovered through conservative management within 1 week of being admitted to the ED. Conclusions: While CO-induced hepatic injury is relatively uncommon, it can be associated with complications and poor neurologic outcome. However, CO-induced hepatic injury was not found to have a statistically significant effect on mortality rate.